A supported liquid membrane system for the selective recovery of rare earth elements from neodymium-based permanent magnets. Issue 10 (2nd July 2016) - Kim, Daejin; Powell, Lawrence; Delmau, Lætitia H.; Peterson, Eric S.; Herchenroeder, Jim; Bhave, Ramesh R.
ABSTRACT: The rare earth elements (REEs) play a vital role in the development of green energy and high-tech industries. In order to meet the fast-growing demand and to ensure sufficient supply of the REEs, it is essential to develop an efficient REE recovery process from post-consumer REE-containing products. In this research effort, we have developed a supported liquid membrane system utilizing polymeric hollow fiber modules to extract REEs from neodymium-based magnets with neutral extractants such as tetraoctyl digylcol amide (TODGA). The effect of process variables such as REE concentration, molar concentration of acid, and membrane area on REE recovery was investigated. We have demonstrated the selective extraction and recovery of REEs such as Nd, Pr, and Dy without co-extraction of non-REEs from permanent NdFeB magnets through the supported liquid membrane system. The extracted REEs were then recovered by precipitation followed by the annealing step to obtain crystalline REE powders in nearly pure form. The recovered REE oxides were characterized by X-ray diffraction, scanning electron microscope coupled with energy-dispersive X-ray spectroscopy, and inductively coupled plasma–optical emission spectroscopy.